2007
DOI: 10.1002/prot.21811
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a secondary vitamin D3 binding site of milk β‐lactoglobulin

Abstract: Beta-lactoglobulin (beta-LG), one of the most investigated proteins, is a major bovine milk protein with a predominantly beta structure. The structural function of the only alpha-helix with three turns at the C-terminus is unknown. Vitamin D(3) binds to the central calyx formed by the beta-strands. Whether there are two vitamin D binding-sites in each beta-LG molecule has been a subject of controversy. Here, we report a second vitamin D(3) binding site identified by synchrotron X-ray diffraction (at 2.4 A reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 58 publications
8
116
0
Order By: Relevance
“…All members of the lipocalin family contain a β-barrel, shaped into a calyx, composed of eight antiparallel β-strands (Flower, 1996). It has been suggested that βlg binds hydrophobic ligands in its internal calyx, in a crevice near the α-helix on the external surface of the β-barrel and near the interface of βlg dimers (Lange et al, 1998, Wang et al, 1998, Wu et al, 1999, Muresan et al, 2001, Kontopidis et al, 2004, Forrest et al, 2005, Dong et al, 2006, Yang et al, 2008. However, the binding sites and stoichiometries of ligands have been controversial (Wang et al, 1998, Wu et al, 1999, Kontopidis et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…All members of the lipocalin family contain a β-barrel, shaped into a calyx, composed of eight antiparallel β-strands (Flower, 1996). It has been suggested that βlg binds hydrophobic ligands in its internal calyx, in a crevice near the α-helix on the external surface of the β-barrel and near the interface of βlg dimers (Lange et al, 1998, Wang et al, 1998, Wu et al, 1999, Muresan et al, 2001, Kontopidis et al, 2004, Forrest et al, 2005, Dong et al, 2006, Yang et al, 2008. However, the binding sites and stoichiometries of ligands have been controversial (Wang et al, 1998, Wu et al, 1999, Kontopidis et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Since LG is a molten globule with a heating for 16 min (Table 1). 26 To confirm it further, we monitored the binding of heated LG (100°C for 16 min) with various amounts of vitamin D 3 , and a stoichiometry of 1:1 was observed between heat-denatured LG and vitamin D 3 using the same fluorescence quenching analysis. 26 Taking the previous pH and thermal experiments together (Table 1), we concluded that a thermally stable site (defined as an exosite) beyond the calyx exists for vitamin D 3 binding.…”
Section: Resultsmentioning
confidence: 93%
“…26 To confirm it further, we monitored the binding of heated LG (100°C for 16 min) with various amounts of vitamin D 3 , and a stoichiometry of 1:1 was observed between heat-denatured LG and vitamin D 3 using the same fluorescence quenching analysis. 26 Taking the previous pH and thermal experiments together (Table 1), we concluded that a thermally stable site (defined as an exosite) beyond the calyx exists for vitamin D 3 binding. In the present study, we located the secondary vitamin D 3 binding site of LG using bioinformatic analysis to narrow the region of potential binding sites, the search of extra electron density around the potential binding sites of the cocrystal prepared on previous crystallographic study, 20 and a rationally designed crystallographic approach for obtaining cocrystals with sufficient quality and ligand occupancy.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations